RNA modification is the mark and strategy for host-microbe interactions - Ye Tian; Xiaoyun Wang (Cellular and Molecular Life Sciences)
Abstract Pathogenic microbes need to adapt to host environments during infection. With advances in sequencing technologies, RNA modifications have been shown to play a pivotal role in pathogen adaptability on a global scale. In this review, we highlight recent advances in RNA modifications that are utilized as the strategy for pathogens to survive in the host. Specifically, we summarize the studies of RNA modifications in the pathogenic bacteria, fungi, viruses, parasites, and host. We also discuss the anti-infection potential of targeting RNA modifications.